Detection of Blood and Rhesus With Arduino Uno Mega 2560: Detection of Blood and Rhesus With Arduino Uno Mega 2560 - Raka Alvianda; Agung Triayudi; Deny Hidayatulloh (Institute of Computer Science (IOCS), 2020)
Detection of blood type is usually done manually by the process of testing red blood cells with the serum to see Whether clots will occur or not clot. The purpose of this study is to design a tool that will be used to detect blood types. In this study, the detection of groups was designed with electronics using ABO blood groups. This tool is designed using the Arduino Mega 2560 Module as a device, three light sensors, LED as a transmitter and a diode as a receiver. Clumping or non-clumping sensors from serum samples have been mixed. Furthermore, it will send a voltage to be conditioned by a comparator circuit and then sent to the Arduino for processing and the results will be displayed on the LCD, From testing 25 samples the percentage level can be calculated that is 100%.